Gestión de ingresos y gastos en el comercial Casa Eres en el periodo 2020 - Rojas Aguirre, Alexis Javier (2021)
The commercial CASA ERES is located in the city of Babahoyo whose economic activity is the sale of clothes for all types of people and all ages, in addition to selling bicycles, fabrics, toys, etc. Within the commercial house CASA ERES there are many shortcomings due to the fact that it does not have a system that gives precise information about its income and expenses. For this reason, the commercial has had many losses. In 2020, problems arose due to the COVID-19 pandemic which led to the commercial ending with large losses in the first period, but nevertheless it was sustained thanks to the fact that in the second period its profits increased, but still at the end of the year there was a decrease in their income. This study is based on the research sub-line "financial, tax and social commitment management" of the Babahoyo technical university, since in this it is proposed how businesses must register their accounting operations keeping a control.